VISUALISASI BODY-SHAMING DALAM FOTOGRAFI EKPRESI - Sanjaya, I Gusti Katon Dwi; Darmawan, I Dewa Made; Nindhia, Cokorda Istri Puspawati (Retina Jurnal Fotografi, 2022)
This project is entitled "Visualization of body shaming in Expression Photography" in which the author discusses the impact that polemics can have on society. The negative effects of physical bullying, such as body shaming, on a person's mental health, including an overall loss of confidence and self-esteem. body shaming acts are performed with intentional elements, both verbally and non-verbally, such as on social media especially Instagram. The initial concept was developed into an Independent Study/Project using expression photos, its creation involves several stages, including exploration, experimentation, forming, and finishing, with the use of theories that relate to body shaming, expression photography theory, and semiotic theory. Several expressive photographs depict the feelings experienced by victims of body shaming and the body parts that are objects of humiliation as a result of this Study/Project Independent. These works are entitled as Desperate, Fracture and Impenetrable. This project was conceived as a means of creating awareness of poor and incorrect behaviour so that people would not commit acts of verbal bullying that led to body shaming. Keywords: Visualization, Body-Shaming, Expression Photography